The Role of Pancasila Values in Overcoming the Lost Generation Among Secondary School Students in South Sulawesi - Aprisal, Wahyu; Tahir, Heri; Heri, Ririn Nurfaathyrani; Suyitno, Imam; Najamuddin, Najamuddin; Sahabuddin, Romansyah (Universitas Muhammadiyah Makassar, 2025)
The urgency of this research arises from the growing indications of a “lost generation” among Indonesian adolescents, characterized by moral degradation, weakened spiritual awareness, diminished social empathy, and identity confusion amid rapid digital and socio-cultural change. This study aims to analyze the role of implementing Pancasila values, particularly Belief in One Almighty God (Principle 1) and Just and Civilized Humanity (Principle 2), in addressing the lost generation phenomenon among students at a public senior high school in South Sulawesi Province. This descriptive qualitative study employed classroom and school-wide observations, in-depth interviews with the Principal, PPKn teachers, guidance and counseling (BK) teachers, and students, as well as document analysis; the data were analyzed using the Miles and Huberman interactive model, including data condensation, data display, and conclusion drawing/verification, supported by triangulation to ensure validity. The findings show that Principle 1 functions as the primary moral foundation and is operationalized through the integration of Pancasila values in the PPKn curriculum, religious education and activities, contextual gratitude projects (such as environmental and social-care initiatives), and school policies that guarantee religious freedom and tolerance. Principle 2 is realized through the systematic cultivation of universal moral values—honesty, responsibility, respect, and empathy—embedded in habituation programs (honesty journals, cooperative learning), strengthened by peaceful conflict-management strategies (peer mediation) and a zero-tolerance anti-bullying procedure. These integrated practices collectively help mitigate symptoms associated with a lost generation by reinforcing students’ sense of life meaning, spiritual consciousness, and humane, responsible self-identity. The novelty of this research lies in proposing an integrated school-based model that links spiritual formation and humanitarian ethics within a Pancasila framework specifically to the prevention of a lost generation. This study contributes conceptually to the refinement of Pancasila-based democratic citizenship education and practically to the design of value-based interventions for school leaders, PPKn teachers, and counselors in similar educational contexts.